Clinical Features of the Course of Musculoskeletal Infection after Local Administration of Glucocorticoids - Hrytsai, M.P.; Tsokalo, V.M.; Kolov, H.B.; Sabadosh, V.I. (TERRA ORTHOPAEDICA, 2022)
Summary. In the treatment of patients with inflammatory and degenerative-dystrophic lesions of the joints, soft tissues and ligaments, local administration of drugs is often used in practice, usually (mainly) glucocorticoids.Objective: to determine the place and role of local administration of glucocorticoids in the occurrence and development of musculoskeletal infection.Materials and Methods. The peculiarities of the occurrence and development of infectious complications, their clinical manifestations, laboratory and anamnestic data after local administration of glucocorticoids in 56 patients aged 24 to 78 years were analyzed.Results. 44 patients had moderate and severe subcompensated comorbidities. Betamethasone was the most commonly used for injections (32 patients, 57.2%). Glucocorticoids were administered intra-articularly to 43 (76.8%) patients: knee joint (37.5%), shoulder (25.0%), ankle (7.1%), hip (3.6%), elbow and 1st metatarsophalangeal (1 case each). In other cases (bursitis, enthesitis, etc.), glucocorticoids were administered paraarticularly. It was a single injection only in 32%; the rest of patients were injected 2 – 20 times. In 96% of cases, monocultures were microbiologically isolated (S.aureus in 52%). At the time of hospitalization, the acute stage of the infectious process was detected in 22 (39.3%) patients, subacute in 16 (28.6%), and chronic active fistula phase in 18 (32.1%). All cases of clinically similar manifestations are systematized into groups of symptom complexes – clinical variants: 1) abscess and/or phlegmon of paraarticular soft tissues, necrotizing fasciitis; 2) septic bursitis; 3) septic arthritis (synovitis); 4) septic destructive arthritis; 5) osteomyelitis.Conclusions. We found no clinical differences depending on the drugs used. The most important reasons for the development of infectious complications are ignoring the principles of dosing, multiplicity and time intervals of administration, unreasonable repeated use, and the presence of serious subcompensated comorbidities, which should be considered as a relative contraindication and as a risk factor.